Coxiella burnetii seroprevalence in sheep herd from Paraguay: First evidence of bacterial circulation in the country - França, Danilo Alves de [UNESP]; Silva, Filipe Pereira da; Zanini, Dayane da Silva [UNESP]; Iglesias, Lorena; Portillo, Laura; Cortez, Herminia; Biondo, Alexander Welker; Duré, Ana Íris de Lima; Silva, Marcos Vinicius Ferreira; Miret, Jorge; Langoni, Helio [UNESP] (Elsevier, 2024)
Coxiella burnetii is the agent of Q fever, a disease that poses risks to public health and damages livestock. We discovered the circulation of C. burnetii for the first time in Paraguay, based on the seropositivity of a flock of >300 sheep. The animals were tested by IFA for anti-C. burnetii antibodies and by SAM for anti-Leptospira spp. antibodies, an important differential diagnosis for reproductive disorders in sheep in Paraguay. C. burnetii seropositivity was determined in 45%, in contrast to Leptospira spp. which had no reactive samples. Cases of miscarriage and fetal resorption were associated with high seropositivity titers. This study suggests the circulation of a unique genotype in the country and an imminent risk to public health, since in addition to being highly transmissible and infectious to humans, Q fever is still not a cause for concern on the part of government and health agencies in the country.
Keywords: Emerging disease; Q fever; Risk factors; Seroepidemiology; Seroprevalence; Small ruminants; Zoonoses